EFEKTIFITAS EVALUASI DAN PENGUKURAN DALAM PENGEMBANGAN KURIKULUM - Arief Dwi Kurniawan; Ginanjar Budi Utama; Ade Ruswatie (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to analyze the effectiveness of evaluation and measurement in the curriculum development process as an important instrument to ensure the quality of adaptive and sustainable education. The approach used is qualitative descriptive, with a focus on an in-depth understanding of evaluation and measurement practices as carried out by teachers, curriculum developers, and education stakeholders. Data was obtained through the study of curriculum documents, assessment instruments, evaluation reports, and relevant education policies, then analyzed by data reduction, categorization, and thematic interpretation techniques. The results show that evaluation serves as an integral process in the curriculum development cycle, not just a final assessment, but rather as a diagnostic tool for continuous improvement. The evaluation of the CIPP (Context, Input, Process, Product) model and the formative-summative approach has been proven to be able to provide a comprehensive overview of the strengths and weaknesses of the curriculum. Meanwhile, measurement plays a specific role as a specific part of evaluation that produces quantitative and qualitative data through instruments such as written tests, observations, interviews, portfolios, and questionnaires. The synergy between evaluation and measurement allows the curriculum not only to be a normative document, but to be truly effective in improving student competence, improving the quality of learning, and adapting to the demands of the digital era and globalization. This study confirms that the effectiveness of evaluation and measurement is determined by the relevance of the instrument to the curriculum objectives, the validity and reliability of the measurement results, and the real contribution to curriculum improvement. Thus, systematic and continuous evaluation and measurement are the key to realizing a dynamic, inclusive, and oriented curriculum to improve the quality of national education.